Transition from saturable absorption to reverse saturable absorption in multi-layered WS2 nanosheets. (April 2021) - Karmakar, Srikanta; Chatterjee, Udit; Kumbhakar, Pathik
Graphical abstract: Highlights: NLO properties of trilayer WS2 NSs have been investigated by Z-Scan Technique. The transformation of 1PA to 2PA is observed in trilayer WS2 NSs. The highest β2PA of trilayer WNSs is 1.5 times higher to that of multilayer WNSs. The Im χ (3) for trilayer WNSs have been calculated to be 4.24 × 10 −13 esu. Abstract: By employing the Z-scan technique, the nonlinear optical (NLO) properties of multi-layered WS2 nanosheets (WNSs) are investigated using pulsed (10 ns) laser irradiation having wavelength of 532 nm. In the trilayer WNSs, the transformation from saturable absorption (SA) to reverse saturation absorption (RSA) is clearly observed only when the magnitude of incident pump intensity exceeds 0.68 GW/cm 2 . The saturation intensity in the case of SA for the used sample is found to be 0.53 ± 0.03 GW/cm 2 . The SA behaviour appears at low intensity due to one photon absorption (1PA) originated from the direct transition at B excitonic peak. This is confirmed from the measured photoluminescence properties of trilayer WNSs. Further, with the increase of laser intensity, the transformation of 1PA to two-photon absorption (2PA) occurs only for trilayer WNSs. It is observed that at the highest used intensity of 0.93 GW/cm 2, trilayer WNSs exhibits a large 2PA. A comprehensive analysis of the experimental data of Z-scan enables us to determine a value of 1.42 ± 0.01 cm/GW for the highest 2PA coefficient ( β2PA ) and this value is 1.5 times higher than those obtained for the multilayer and penta-layer WNSs. The calculated value of the imaginary part of the third-order NLO susceptibility ( Im χ (3) ) of the trilayer WNSs is 4.24 × 10 −13 esu. The properties of transition from SA to RSA in thinned layered of WNSs make these materials favourable for designing different optoelectronic devices.